Frequency of Hepatitis B and C Viruses, and HIV Among Drug Addicts in the Eastern Anatolia, Turkey - Karabulut, Nuran; Bulut, Yasemin; Telo, Selda (Kowsar Publ, 2015)
Background: Hepatitis B, hepatitis C and HIV infections constitute serious healthcare problems worldwide. Objectives: There are a limited number of studies regarding the prevalence of hepatitis B, hepatitis C and HIV infections among the drug addicts in Turkey; hence, the current study aimed to determine the frequency of these infections among 235 drug addicts treated in a drug addiction treatment centre/Elazig, Turkey Patients and Methods: HBsAg, anti-HBs, anti-HCV and anti-HIV tests in 235 drug addicts were studied by ELISA technique. Urine samples obtained from drug addicts were analyzed for cannabis, opiate and cocaine metabolites. Results: All the 235 drug users were males, and their mean age was 30.69 +/- 9.494 years; 112(47.7%) of them were in the age group ranging 20 - 29 years (P < 0.05). Of 235 drug addicts, 113 (48.1%) and US (48.9%) were only cannabis and opiate users, respectively. In urine samples of seven (3%) drug addicts both cannabis and opiate metabolites were detected. Cocaine was detected in none of the urine samples. The frequencies of HBsAg, anti-HBs and anti-HCV among drug addicts were 2.6%, 38.3%, and 9.4%, respectively. None of the drug addicts was positive for HIV.Anti-HCV was more prevalent in opiate users than in cannabis users: 15.7% vs.1.8%(P < 0.001). Conclusions: The obtained results showed that HCV infection was an alarming problem among opiate users in the eastern part of Turkey. It is suggested to rapidlydiagnose the infected persons; thus preventive measures and appropriate control may limit further transmission of these infections.
Keywords: Hepatitis B; Hepatitis C; HIV; Opioid-Related Disorders; Cannabis; Cocaine; Drug Users